PENGARUH PENGEMBANGAN KARIR TERHADAP KEPUASAN KERJA KARYAWAN MELALUI MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING (STUDI KASUS PADA HOTEL GRASIA SEMARANG) - Lisdiani, Vendriana; Ngatno, Ngatno (Jurnal Ilmu Administrasi Bisnis, 2017)
Human resource is the most important factor in a creat the purpose of business administration. Grasia hotel confront high turnover. Many factors that affect them career development and job satisfaction.This study intend to determine the effect of career development towards job satisfaction, career development towards work motivation, job satisfaction towards work motivation, and career development towards job satisfaction through work motivation,In this study the population are official employee of Grasia Hotel Semarang which is 80 samples. The type of this research is explanatory research with quantitative approach. The analysis technique used are correlation test, determination test, simple regression test, signification test, sobel test, mediation test using SPSS version 16 application.The result of this research indicate that the career development has a significant effect towards job satisfaction, career development has significant effect towards work motivation, job satisfaction has effect towards work motivation, career development has effect towards job satisfaction through work motivation partial mediation. Each hypothesis test has a significant 0.00.Based on this, researchers suggest that additonal and maximizing the work motivation by increasing the frequency employee morale by giving bonuses and reward. In addition, holding job training with mentor guidance.